Photo-induced atom transfer radical polymerization of styrene using a highly active claw-type Schiff-base ligand. (5th June 2022) - Xu, Xiaoling; Peng, Bin; Hong, Mei; Wang, Tianheng; Fan, Liyuan; Bao, Chunyang; Zhang, Qiang
Graphical abstract: Highlights: Tris[ N -(2-(4-(dimethylamino)pyridylmethyl)-2-iminoethyl]amine is a highly active claw-type ligand for Photo-ATRP. After Photo-ATRP of styrene, the system appeared stratification and upper-layer PSt could be directly separated from the system. Abstract: The use of a tripodal Schiff base, tris[ N -(2-(4-(dimethylamino)pyridylmethyl)-2-iminoethyl]amine (Py NMe2 3 Tren), as a highly active claw-type ligand for photo-induced atom transfer radical polymerization (Photo-ATRP) is reported. CuBr2 / Py NMe2 3 Tren is employed as the catalyst for Photo-ATRP of styrene (St) under the irradiation of visible or ultraviolet light. Well-defined polystyrene (PSt) could be synthesized with high chain-end functionality confirmed by in situ chain extension and PSt-Br macroinitiator for the secondary polymerization of St. Through switching the light "on" and "off", temporal control of Photo-ATRP was successfully demonstrated. After the polymerization, the reaction system appeared stratification and the upper layer PSt could be facilely separated from the system.